Immunostimulatory RNA leads to functional reprogramming of myeloid-derived suppressor cells in pancreatic cancer - Metzger, Philipp (J Immunother Cancer, 2019)
BACKGROUND: The tumor microenvironment (TME) combines features of regulatory cytokines and immune cell populations to evade the recognition by the immune system. Myeloid-derived suppressor cells (MDSC) comprise populations of immature myeloid cells in tumor-bearing hosts with a highly immunosuppressive capacity. We could previously identify RIG-I-like helicases (RLH) as targets for the immunotherapy of pancreatic cancer inducing immunogenic tumor cell death and type I interferons (IFN) as key mediators linking innate with adaptive immunity. METHODS: Mice with orthotopically implanted Kras(G12D) p53(fl/R172H) Ptf1a-Cre (KPC) pancreatic tumors were treated intravenously with the RLH ligand polyinosinic-polycytidylic acid (poly(I:C)), and the immune cell environment in tumor and spleen was characterized. A comprehensive analysis of the suppressive capacity as well as the whole transcriptomic profile of isolated MDSC subsets was performed. Antigen presentation capability of MDSC from mice with ovalbumin (OVA)-expressing tumors was investigated in T cell proliferation assays. The role of IFN in MDSC function was investigated in Ifnar1(−/−) mice. RESULTS: MDSC were strongly induced in orthotopic KPC-derived pancreatic cancer, and frequencies of MDSC subsets correlated with tumor weight and G-CSF serum levels, whereas other immune cell populations decreased. Administration of the RLH-ligand induced a IFN-driven immune response, with increased activation of T cells and dendritic cells (DC), and a reduced suppressive capacity of both polymorphonuclear (PMN)-MDSC and monocytic (M)-MDSC fractions. Whole transcriptomic analysis confirmed an IFN-driven gene signature of MDSC, a switch from a M2/G2- towards a M1/G1-polarized phenotype, and the induction of genes involved in the antigen presentation machinery. Nevertheless, MDSC failed to present tumor antigen to T cells. Interestingly, we found MDSC with reduced suppressive function in Ifnar1-deficient hosts; however, there was a common flaw in immune cell activation, which was reflected by defective immune cell activation and tumor control. CONCLUSIONS: We provide evidence that the treatment with immunostimulatory RNA reprograms the TME of pancreatic cancer by reducing the suppressive activity of MDSC, polarizing myeloid cells into a M1-like state and recruiting DC. We postulate that tumor cell-targeting combination strategies may benefit from RLH-based TME remodeling. In addition, we provide novel insights into the dual role of IFN signaling in MDSC’s suppressive function and provide evidence that host-intrinsic IFN signaling may be critical for MDSC to gain suppressive function during tumor development.